A note on cloud computing security. (6th April 2020) - Garg, Deepak; Sidhu, Jagpreet; Rani, Shalli
Cloud computing has become an emerging technology which has huge impact. Existing security algorithms cannot meet the needs of cloud computing users as security issues have become increasingly prominent, becoming an important factor restricting the development of cloud computing. Research community has immensely focused on developing and optimising security techniques to overcome this hurdle in cloud. Due to huge literature it becomes difficult to comprehend overall structure and advancements. This domain needs an analytic approach to completely understand the problem domain that is why this article represents same in specific context of security. Further, a notion on security issues in cloud computing with respect to vulnerabilities, threats and attacks is discussed. Paper also proposed two research evaluation parameters that are effective citation and effective impact factor for better appreciation. Article also analyses patterns, trends and other factors for directing research activities. Finally, a global research trends on security domain are evaluated and analysed.